Pengaruh Debt Default, Mandatory Disclosure, dan Ukuran Perusahaan Terhadap Opini Audit Going Concern dengan Audit Delay sebagai Variabel Moderasi - Sinthia Maida Mahsa; Abriandi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research discusses the effect of debt default, mandatory disclosure, and firm size on going concern audit opinion with audit delay as a moderating variable. The population in this reserach are all mining sector companies listed on the Indonesia Stock Exchange (IDX) in 2015 – 2018. The number of samples used in this research are 38 companies with a purposive sampling technique and the number of observations of reserach data obtained was 152. The data analysis methods used are logistic regression and Moderated Regression Analysis (MRA). The result of the research are debt default has a poitive effect on going concern audit opinion, mandatory disclosure has a negative effect on going concern audit opinion and company size has no effect on going concern audit opinion. Audit delay does not moderate the effect of debt default, mandatory disclosure and company size on going concern audit opinion.